Integrating English songs as a teaching strategy: Teachers’ perspectives on enhancing EFL students’ listening comprehension - Farhat Muharrom Annuri; Nailul Authar; Savira Zaniar; Tiyas Saputri; Djuwari Sarkawi (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2025)
This study examines the integration of English songs as a teaching strategy to enhance students’ listening comprehension in EFL classrooms, with a particular focus on teachers’ perspectives. Addressing the limited research on how teachers perceive and implement songs within listening instruction, the study adopts a qualitative descriptive design. Data were collected through semi-structured interviews with six experienced EFL teachers from senior high schools in East Java, Indonesia, and analyzed using a thematic analysis approach. The findings reveal that teachers view English songs as an effective tool for increasing student engagement, facilitating vocabulary development, and improving overall listening skills. Nonetheless, challenges were noted, including the complexity of language used in songs, cultural references unfamiliar to students, and the time required to prepare appropriate materials. The study concludes that, when integrated thoughtfully, English songs can serve as powerful tools for enhancing listening comprehension. The findings also underscore the significance of institutional support and targeted professional development in promoting the practical application of these tools in EFL teaching.